DESAIN TATA LETAK FASILITAS PRODUKSI PADA PENGOLAHAN RIBBED SMOKED SHEET (RSS) DI GUNUNG PASANG PANTI KABUPATEN JEMBER - Bambang Herry Purnomo; Andrew Setiawan Rusdianto; Muhammad Hamdani (JURNAL AGROTEKNOLOGI, 2013)
Industrial layout or production facility is a setting for placing facilities position which considering space limitation in placing machines, flow of material removal etc. Generally the optimal layout design is take a part in determining the efficiency and effectiveness of production activities or maintain the viability of an Industrial. Basically the main goal of this research is to produce an optimal layout of production facilities, one of which is to evaluate the existing layout. The refore we need an optimal facility layout design according to a good material flow patterns, by following the order of process. Direct observation at PDP Gunung Pasang Panti Jember Region, showed less precise placement of production facilities and material flow, causing the displacement of material handling distances become longer and eventually impact on Total Movement becomes high. To determine the layout of each department production facilities in a manner that is efficient use of time study method. As for planning the layout by using layout verification results by comparing the existing layout as a parameter events. The results showed a more efficient layout verification with Total Movement initial displacement distance of 2650.44 meters to 2469.46 meters or the distance may be shortened by 6.83%. As for the time of the original conveyance of 422.5 seconds to 392.8 seconds or experiencing a savings of 7.03%.Keywords: layout, time study method, total movement